A Periplasmic Lanthanide Mediator, Lanmodulin, in Methylobacterium aquaticum Strain 22A - Fujitani, Yoshiko; Shibata, Takeshi; Tani, Akio (Frontiers in Microbiology, 2022)
Methylobacterium and Methylorubrum species oxidize methanol via pyrroloquinoline quinone-methanol dehydrogenases (MDHs). MDHs can be classified into two major groups, Ca2+-dependent MDH (MxaF) and lanthanide (Ln3+)-dependent MDH (XoxF), whose expression is regulated by the availability of Ln3+. A set of a siderophore, TonB-dependent receptor, and an ABC transporter that resembles the machinery for iron uptake is involved in the solubilization and transport of Ln3+. The transport of Ln3+ into the cytosol enhances XoxF expression. A unique protein named lanmodulin from Methylorubrum extorquens strain AM1 was identified as a specific Ln3+-binding protein, and its biological function was implicated to be an Ln3+ shuttle in the periplasm. In contrast, it remains unclear how Ln3+ levels in the cells are maintained, because Ln3+ is potentially deleterious to cellular systems due to its strong affinity to phosphate ions. In this study, we investigated the function of a lanmodulin homolog in Methylobacterium aquaticum strain 22A. The expression of a gene encoding lanmodulin (lanM) was induced in response to the presence of La3+. A recombinant LanM underwent conformational change upon La3+ binding. Phenotypic analyses on lanM deletion mutant and overexpressing strains showed that LanM is not necessary for the wild-type and XoxF-dependent mutant’s methylotrophic growth. We found that lanM expression was regulated by MxcQE (a two-component regulator for MxaF) and TonB_Ln (a TonB-dependent receptor for Ln3+). The expression level of mxcQE was altered to be negatively dependent on Ln3+ concentration in ∆lanM, whereas it was constant in the wild type. Furthermore, when exposed to La3+, ∆lanM showed an aggregating phenotype, cell membrane impairment, La deposition in the periplasm evidenced by electron microscopy, differential expression of proteins involved in membrane integrity and phosphate starvation, and possibly lower La content in the membrane vesicle (MV) fractions. Taken together, we concluded that lanmodulin is involved in the complex regulation mechanism of MDHs and homeostasis of cellular Ln levels by facilitating transport and MV-mediated excretion.